Pengaruh Brand Image Dan Gaya Hidup Terhadap Keputusan Pembelian Produk Iphone (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang Tahun Angkatan 2018) - Wisesa, Andhika Ghani; Basalamah, Muhammad Ridwan; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research aims to determine the influence of brand image and lifestyle in making decisions to buy iPhone products (study of students from the Faculty of Economics and Business, Islamic University of Malang class of 2018). The population and sample for this research are students from the Faculty of Economics and Business at UNISMA, class of 2018. The sample used is a sample in the form of a purposive sampling method with sample measurement using the Malhotra method. The results of the research are that partially the Brand Image variable has a positive influence on the Purchase Decision of iPhone Products for Students from the Faculty of Economics and Business, Islamic University of Malang in the class of 2018. Variables and Lifestyle have a positive influence on the Purchase Decision for iPhone Products for Students from the Faculty of Economics and Business, Islamic University of Malang in the year 2018. Meanwhile, Brand Image and Lifestyle simultaneously influence the Purchase Decision of iPhone Products for Students from the Faculty of Economics and Business, Islamic University of Malang, class of 2018. Keywords: Brand Image, Lifestyle, and Purchasing Decisions.